THE ROLE OF SERVICE QUALITY AGILITY, COMPETENCE, AND ORGANIZATIONAL COMMITMENT IN IMPROVING EMPLOYEE PERFORMANCE - Fitrio, Tomy; Remofa, Yudha; Hardi, Hardi; Ismail, Yusof (Universitas Brawijaya, Indonesia, 2023)
Employees are assets for the company. Therefore high employee performance can improve company performance in achieving goals. The current research was done to develop a conceptual model related to competency, organizational commitment, service quality agility, and employee performance. In this case, data involved were obtained from 127 BUMN Bank employees. The information was prepared to utilize PLS Structural Equation Modeling. This study suggested service quality agility as a technique to raise worker productivity. The study further revealed that competence and organizational commitment mediated by service quality agility improve employee performance. Therefore, this result supports the hypothesis of the significance of service quality agility in improving employee performance. The findings from this study can be used as a strategy for improving employee performance. This result also strengthens the human motivation theory, in which employees working with suitable competence, high commitment, and high motivation in providing services can improve employee and organizational performance. Future research can focus on service quality agility by expanding the research subject to other business companies related to customer service, and the results may vary.